LEGAL ANALYSIS OF THE PROVISIONS ON THE DEATH PENALTY IN THE CRIMINAL CODE - Dedy Irawan; Diding Rahmat; Ardison Asri (JILPR Journal Indonesia Law and Policy Review, 2026)
Capital punishment is the most severe form of punishment in the Indonesian criminal justice system and remains a controversial issue that sparks debate between the need to uphold justice and the protection of human rights, particularly the right to life. Under the old Criminal Code, capital punishment was included as a primary punishment that could be imposed on perpetrators of serious crimes such as premeditated murder, terrorism, treason, and drug trafficking. Meanwhile, the new Criminal Code, as specified in Law No. 1 of 2023, introduces significant changes in the regulation of the death penalty. The death penalty is no longer positioned as the primary punishment but rather as a conditional alternative punishment, which is only imposed if other penalties are deemed insufficient to achieve justice. This study aims to examine the differences in the regulation of the death penalty in the old and new Criminal Codes and to analyze the considerations of judges in imposing the death penalty based on a study of Decision No. 32/Pid.Sus/2025/PN Pts. The approach used is normative legal with a descriptive analysis method. The results of the study show a shift in the criminal law paradigm from a retributive approach to a more restorative and humanistic approach. In the new Criminal Code, the death penalty can be imposed with a probation period of 10 years, and if during that period the convict demonstrates good attitude and behavior, the sentence can be changed to life imprisonment or a fixed term of imprisonment. The regulation of the death penalty in the new Criminal Code reflects the state's efforts to maintain the deterrent effect on serious crimes while upholding the principles of humanity and balanced justice.